Agro-forfstry in India - Sharma, R. A. (Indian Forester, 1992)
The current status of agroforestry practices and research is presented in this paper. Main interactions between the components of agroforestry are highlighted It is argued that there is lack of quantitative information about the complex interactions although qualitative And judge-mental information is available from the villagers who have long since practiced the traditional agrororestry systems. Finally the criteria for evaluating agroforestry are presented and the current state of research discussed.